Clinical Psychologists' Views of Intensive Interaction as an Intervention in Learning Disability Services. (20th May 2013) - Berry, Ruth; Firth, Graham; Leeming, Catherine; Sharma, Vishal
<x xml:space="preserve">Abstract</x> Intensive Interaction was initially developed in the 1980s as an educational approach for developing social communication and engagement with people with severe or profound intellectual disabilities and/or autism. Intensive Interaction has subsequently been adopted by a range of practitioners and professionals working in learning disability services and has a broad multi‐disciplinary acceptance, being recommended in a number of UK governmental guidance documents. Despite this, there has been limited work on developing a deeper psychological understanding of the approach. This study utilises a qualitative description/thematic analysis approach to explore how clinical psychologists conceptualise the approach with regard to currently accepted psychological theories, as well as looking at other factors that influence their adoption and advocacy. The sample deliberately consisted of eight NHS (National Health Service) clinical psychologists known to be using or advocating the use of Intensive Interaction with people with a learning disability. The results of this study indicate that although the participants referred to some theories that might explain the beneficial outcomes of Intensive Interaction, these theories were rarely explicitly or clearly referenced, resulting in the authors having to attribute specific theoretical positions on the basis of inductive analysis of the participants' responses. Moreover, the participants provided varying views on how Intensive Interaction might be conceptualised, highlighting the lack of a generally accepted, psychologically framed definition of the approach. In conclusion, it was felt that further research is required to develop a specifically psychological understanding of Intensive Interaction alongside the formation of a Special Interest Group, which might have this task as one of its aims. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Messages There appeared to be a limited recognition amongst the participants of the specific psychological theories that can be seen to explain the beneficial outcomes of Intensive Interaction. The participants were found to differ in how they explained the approach and typically used everyday 'non‐psychological' language or individual concepts/terms rather than clearly or extensively referencing particular theoretical models. The participants appeared to differ in the range of clients who they thought might benefit from Intensive Interaction. An Intensive Interaction Special Interest Group, which includes clinical psychologists, should be set up to instigate psychologically informed theory development and research with the broader aims of fostering greater understanding and adoption of Intensive Interaction within services for people with severe or profound intellectual disabilities and/or autism.